The Problem of the Chinese Basketball Association Competing for the Championship - He Zhang (International Journal of Engineering and Management Research, 2020)
In China, basketball is a very popular sport and is loved by the people. The Chinese Basketball Association is China's highest-level basketball league. While watching the game, more and more people want to predict the outcome of the game. There are currently 14 teams participating in the game. According to the rules of the match, the game is divided into two stages: regular season and playoffs. Each game must have a victory, and each team has a fixed number. This article is based on about 100 historical score data from each team for four years, By building a mathematical model, Analyze and calculate the winning probability of the 14 teams. And give a qualitative analysis of the level of the 14 teams in the CBA league.